Repurposing Consumer Products as a Gateway to Just-in-Time Communication - O'Brien, Amanda; O'Brien, Meghan; Schlosser, Ralf W.; Yu, Christina; Allen, Anna A.; Flynn, Suzanne; Costello, John; Shane, Howard C. (Seminars in Speech and Language, 2017)
The rich feature set and flexibility of mobile technology offers a host of novel opportunities to provide specific and timely supports to individuals with communication and memory disorders. These “just-in-time” (JIT) supports can be used as prompts, reminders, rewards, strategies to increase independence, and expressive language supports for children and adults with communication and memory disorders. The purpose of this article is to examine current research on, and propose future directions for, repurposing consumer products to enhance JIT communication within the field of augmentative and alternative communication. Initially, a brief history of JIT supports will be reviewed, including a timeline and history of JIT-enabling technology. Next, the taxonomy of JIT supports will be applied to current research in both individuals with autism spectrum disorder and individuals with acquired communication disorders (e.g., acquired brain injury, amyotrophic lateral sclerosis) to illustrate current clinical implications and evaluate current limitations of JIT supports. Finally, future directions for research and expanded use of consumer products to provide JIT supports will be discussed.
Keywords: Just-in-time; augmentative and alternative communication; ASD; acquired brain injury; amyotrophic lateral sclerosis